2013
DOI: 10.1166/jnn.2013.6025
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cobalt Content on Wear and Corrosion Behaviors of Electrodeposited Ni–Co/WC Nano-Composite Coatings

Abstract: Metal-ceramic composite coatings are widely used in automotive and aerospace industries as well as micro-electronic systems. Electrodeposition is an economic method for application of these coatings. In this research, nickel-cobalt coatings reinforced by nano WC particles were applied on carbon steel substrate by pulse electrodeposition from modified Watts bath containing different amounts of cobalt sulphate as an additive. Saccharin and sodium dodecyl sulphate (SDS) were also added to electroplating bath as g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 3 publications
0
5
0
2
Order By: Relevance
“…This means also that MS is more corroded in the tested solutions than LRBS specimens. It is widely recognized that the presence of other elements such as Cr and Co in LRBS specimens reinforced the corrosion resistance of LRBS in comparison with MS [3,4].…”
Section: Potentiodynamic Polarization Curves (Ppc's)mentioning
confidence: 99%
“…This means also that MS is more corroded in the tested solutions than LRBS specimens. It is widely recognized that the presence of other elements such as Cr and Co in LRBS specimens reinforced the corrosion resistance of LRBS in comparison with MS [3,4].…”
Section: Potentiodynamic Polarization Curves (Ppc's)mentioning
confidence: 99%
“…33 The WC nanoparticles (NPs) contribute to nickel grain size reduction during codeposition while hardness and wear resistance of the composite coating are enhanced. [34][35][36] Although the coatings have excellent wear resistance, they are intrinsically hydrophilic as the embedded WC particles in the coatings have strong covalent bonds and high surface energy. 37 Therefore, developing a simple, inexpensive approach for a robust superhydrophobic surface is high required.…”
Section: Introductionmentioning
confidence: 99%
“…Various solid particles, such as SiC, 10 CeO 2 , 11 Al 2 O 3 (Ref. 12) and WC, 13 have been incorporated into the NiCo coating matrix through electrochemical methods. However, limited research has been so far reported on the preparation and property of electrodeposited Ni-CoTiO 2 composite coatings, 14,15 and the existing research focused on the corrosion property of composite coatings.…”
Section: Introductionmentioning
confidence: 99%